12+6(5-2x)=6

Simple and best practice solution for 12+6(5-2x)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12+6(5-2x)=6 equation:


Simplifying
12 + 6(5 + -2x) = 6
12 + (5 * 6 + -2x * 6) = 6
12 + (30 + -12x) = 6

Combine like terms: 12 + 30 = 42
42 + -12x = 6

Solving
42 + -12x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + -12x = 6 + -42

Combine like terms: 42 + -42 = 0
0 + -12x = 6 + -42
-12x = 6 + -42

Combine like terms: 6 + -42 = -36
-12x = -36

Divide each side by '-12'.
x = 3

Simplifying
x = 3

See similar equations:

| -(2x-5)-(x-7)=2 | | -10+d=9 | | -x/4-10=-22 | | 96=-8(n-7) | | -3x-2(9+5x)=13-3(2x-3) | | 3(3w-2)=2(3w+3) | | 3(-7-7b)=-189 | | 2z-13=-8z+27 | | 6(1-8a)+7(3a+8)=-73 | | 2x+40=x+2y | | 15/100=23/x | | (4y+8)-(4+3y)=8 | | 4x^2-10x+7=0 | | 6a^2-3a+a-2a^2= | | 9y+27=-72 | | -x/2+3=-12 | | 92=6(r+2)+4r | | 3y-1/2=z | | 90=6(3x+1)-6x | | 5x-12+3x+6=72 | | -40+8=-10+-24 | | 4x^6-3y^4+6x^6+6y^4= | | -2=5+1x | | x/3-9=10 | | 2t+3+3t-4t=4+2 | | 4x^6-3y^4+6x^6y^4-6x^6+6y^4= | | -x-2=6 | | x/2-13=11 | | -53+29=x | | x^2+16=-5 | | -53+23=x | | -53+=x |

Equations solver categories